Hypopyon Uveitis—A Rare Presentation of Intraocular Tuberculosis. (June 2013) - Velu, Jayashree; Agarwal, Shruti; Gupta, Vishali; Sharma, Kusum; Sharma, Aman; Gupta, Amod
Abstract Purpose: Intraocular TB is usually known to present as granulomatous uveitis and presence of hypopyon is extremely rare. The authors describe a case of intraocular tuberculosis presenting as hypopyon uveitis. Design: Case report. Methods: A 40-year-old immunosuppressed woman presented with acute granulomatous uveitis with hypopyon and cervical lymphadenopathy. She underwent aqueous tap for polymerase chain reaction, lymph node biopsy, and PET scan. Results: Molecular diagnostic procedures provided a definite diagnosis of ocular tuberculosis. Antitubercular treatment and steroids led to improvement. Conclusion: Intraocular TB can present as hypopyon uveitis and a high index of suspicion is needed, especially in the endemic areas.